A Negative Feedback Loop in Ultraviolet A-Induced Senescence in Human Dermal Fibroblasts Formed by SPCA1 and MAPK - Xie, Hongfu; Xiao, Xiao; Yi, Yuxin; Deng, Mingxing; Li, Peihui; Jian, Dan; Deng, Zhili; Li, Ji (Frontiers in Cell and Developmental Biology, 2021)
Abstract Secretory pathway calcium ATPase 1 (SPCA1) is a calcium pump localized specifically to the Golgi. Its effects on UVA-induced senescence have never been examined. In our study, expression of SPCA1 was increased in UVA-irradiated human dermal fibroblasts (HDFs) by activating mitogen-activated protein kinase(MAPK) and its downstream transcription factor, c-jun. Dual-luciferase reporter and chromatin immunoprecipitation assays revealed that c-jun regulated SPCA1 by binding to its promoter. Furthermore, down-regulating SPCA1 with siRNA transfection aggravated UVA-induced senescence due to an elevation of intracellular calcium concentrations and a subsequent increase in reactive oxygen species (ROS) and MAPK activity. In contrast, over-expression of SPCA1 reduced calcium overload, consequently lowering the ROS level and suppressing MAPK activation. This alleviated the cellular senescence caused by UVA irradiation. These results indicated that SPCA1 might exert a protective effect on UVA-induced senescence in HDFs via forming a negative feedback loop. Specifically, activation of MAPK/c-jun triggered by UVA transcriptionally up regulated SPCA1. In turn, the increased SPCA1 lowered the intracellular Ca2+ level, probably through pumping Ca2+ into the Golgi, leading to a reduction of ROS, eventually decreasing MAPK activity and diminishing UVA-induced senescence.